The application of Article 20 of Regulation (CE) nº 1008/2008 to competition law. A study of the French case - Estrada Margareto, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
This paper will examine the interpretation and application of Article 20 of Regulation (CE) nº 1008/2008 for the first time since its entry into force, a milestone that has marked an unprecedented development in the defense of the principles governing competition in the European single market. To this end, it will analyze the case that led to its application as a legitimizing instrument for the French regulations prohibiting the exercise of air traffic rights in France on certain routes. This study takes on particular relevance, given the imminent expiration of the deadline to take a decision on maintaining, revoking, or modifying this punitive regulation on air transport within the French jurisdiction.